1970
DOI: 10.1080/0091651x.1970.10380289
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and the Rorschach Whole Response

Abstract: Previous research on the relation between intelligence and Rorschach W responses has produced inconclusive results. The problem was re-examined with methodological improvements. Ss were 58 latency and pre-adolescent boys. Rorschach W responses were coded to Friedman's developmental scoring system, and response frequencies in these categories were correlated with WISC IQ and subtest scaled scores. IQ scores were significantly related to one of two types of developmentally advanced W responses as predicted (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Although there has been some disagreement regarding whether production of high-level whole responses is related to intelligence (Friedman & Orgel, 1964), several authors have demonstrated such a relationship with both children and adults. These findings 7--8 years 10-11 years 13-14 years have been based both on developmental level scores (Goldfried, 1962;Kissel, 1965) and on production of complex whole responses (Allison & Blatt, 1964;Marsden, 1970;Rosenblatt & Solomon, 1954). In the present study, only the data for white subjects are consistent with these findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although there has been some disagreement regarding whether production of high-level whole responses is related to intelligence (Friedman & Orgel, 1964), several authors have demonstrated such a relationship with both children and adults. These findings 7--8 years 10-11 years 13-14 years have been based both on developmental level scores (Goldfried, 1962;Kissel, 1965) and on production of complex whole responses (Allison & Blatt, 1964;Marsden, 1970;Rosenblatt & Solomon, 1954). In the present study, only the data for white subjects are consistent with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…The responses falling at the genetically more mature end of this continuum have been theoretically related to a high level of intellectual competence. This relationship has been most clearly established with respect to the presence of complex whole responses (Blatt & Allison, 1964;Kissel, 196S;Marsden, 1970;Rosenblatt & Solomon, 1954). In contrast, the responses at the lower end of the continuum have been assumed to be related to developmental immaturity and/or to states of cognitive regression (Friedman, 1953).…”
mentioning
confidence: 99%
“…Interestingly, W loaded substantially on the Synthesized Complexity factor but did not exhibit significant correlations with IQ scores. This finding is consistent with earlier studies, which have generally reported that well-articulated and synthesized W responses are related to cognitive ability but that other kinds of W responses are not (Acklin & Fechner-Bates, 1989;Allison & Blatt, 1964;Blatt & Allison, 1963;Marsden, 1970). For example, W responses that are vague or lacking in good form quality do not seem to be related to cognitive ability.…”
Section: Correlations With Wechsler Iqsupporting
confidence: 91%
“…This article describes the association between a number of Rorschach scores and performance on tests of cognitive ability. There has been a long tradition of exploring the relationship between Rorschach scores and measures of intellectual ability, cognitive functioning, and psychological development (e.g., Acklin & Fechner-Bates, 1989; Allison & Blatt, 1964; Brooks, 1979; Charek, Meyer, & Mihura, 2015; Gallucci, 1989; Goldfried, Stricker, & Weiner, 1971; Greenberg & Cardwell, 1978; Gross, Newton, & Brooks, 1990; Ilonen et al, 2000; Marsden, 1970; Meyer, Erdberg, & Shaffer, 2007; Meyer, Giromini, Viglione, Reese, & Mihura, 2015; Mihura, Meyer, Dumitrascu, & Bombel, 2013; O’Neill, O’Neill, & Quinlan, 1976; Ridley, 1987; Ridley & Bayton, 1983; Smith, Bistis, Zahka, & Blais, 2007; Stanfill, Viglione, & Resende, 2013; Wagner, Young, & Wagner, 1992; Wenar & Curtis, 1991; Wood, Krishnamurthy, & Archer, 2003; Zillmer & Perry, 1996). Although results are not uniform, these studies generally have been consistent in demonstrating that measures of psychological sophistication, including general intelligence and youth age, are positively associated with Rorschach scores indicative of cognitive synthesis, conventionality of perception, articulation of the determinants of one’s perceptions, and embellishing perceptions with activity, particularly human activity (see Mihura et al, 2013, and Stanfill et al, 2013, for reviews).…”
mentioning
confidence: 99%